A Case Study On Credit Control In Telekom Sales & Service Sdn. Bhd. : Its Impact On Operational Efficiency And Profitability - Syed Alwi, Sharifah Naimah (2000)
Telekom Sales & Service Sdn. Bhd operational efficiencies were questionable and amongst them was the credit control and collection issue. This had always been a favourite topic discussed at various management meeting, including the Board of Director's meeting.